Changes in Wood Utilization Due to Iron Age Jade Mining in the Western Hexi Corridor: Wood Charcoal Investigations - Liu, Fengwen; Yang, Yishi; Chen, Guoke; Zhang, Shanjia; Zhang, Hucai (Frontiers in Earth Science, 2021)
Charcoal remains from archeological sites are used not only to reconstruct the historical composition of local woodlands but also to examine the history of the human use of wood. Nevertheless, key questions such as how and why people may have selected particular woody taxa from locations long distances from their habitat have rarely been addressed. In the present study, we analyze charcoal remains from the ancient Jingbaoer (JBR) jade mine in the Mazong Mountains (Mazong Shan) of Northwest China to explore patterns in the collection and use of wood by Iron Age people. Factors affecting the choice of wood collected at the JBR site are discussed by combining the results of pollen records and charcoal analysis. Our results suggest that tamarisk (Tamarix L.), a shrub dominant in the local area, was the main source of wood for JBR miners and was used as firewood depending upon its local availability. The miners may also have used wood from species sourced further away, such as Pinus L. and Picea L., because of the local scarcity of these trees in such a dry environment. The agropastoralist subsistence system practiced by the JBR miners supports the hypothesis of the collection of wood from distant locales. This study highlights diverse patterns of wood collection in an area scarce in woody plants and provides new evidence for understanding how Iron Age people adapted to extremely arid environments.